2018
DOI: 10.3390/en11061352
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Heat Pump–Organic Rankine Cycle Systems for the Storage of Renewable Electricity

Abstract: Storage of electricity from fluctuating renewable energy sources has become one of the predominant challenges in future energy systems. A novel system comprises the combination of a heat pump and an Organic Rankine Cycle (ORC) with a simple hot water storage tank. The heat pump upgrades low temperature heat with excess power. The upgraded heat can drive an Organic Rankine Process using the heat pump in reverse operation mode. This approach allows a comparably efficient storage of excess electricity. Waste heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…Thus, for this purpose, the modeling process incorporates and explores the interaction of the thermal and electrical elements in the building. Similar work focusing on the modeling process and optimization of HVAC systems and energy consumption can be found in [26], [27], [28], [29], and [30].…”
Section: Scientific Context Of the Adream Buildingmentioning
confidence: 94%
“…Thus, for this purpose, the modeling process incorporates and explores the interaction of the thermal and electrical elements in the building. Similar work focusing on the modeling process and optimization of HVAC systems and energy consumption can be found in [26], [27], [28], [29], and [30].…”
Section: Scientific Context Of the Adream Buildingmentioning
confidence: 94%
“…The resulting layout has been already investigated from the thermodynamic point of view in previous studies (Frate et al, 2020), and it can be considered as a standard for TI-PTES systems based on organic fluids. More advanced architectures may be found in literature (as in Staub et al, 2018;Dumont et al, 2019), but here only the standard one is investigated for the sake of simplicity. The investigated TI-PTES layout is reported in Figure 1.…”
Section: System Layoutmentioning
confidence: 99%
“…Several authors investigated the TI-PTES performance with different operating fluids, often using the same fluid for both HT-VCHP and ORC. TI-PTES performance with R365mfc is investigated in Staub et al (2018), butene in Jockenhöfer et al (2018) and Steinmann et al (2019), and R1233zd(E) and R1234yf in Dumont et al (2019). An extensive comparison between 17 fluids is performed in Frate et al (2017a), and R1233zd(E) was found to be the one with the highest efficiency among those with low GWP.…”
Section: Ht-vchp and Orc Working Fluid Choicementioning
confidence: 99%
See 2 more Smart Citations